Sliding mode control strategy of grid-forming energy storage converter with fast active support of frequency and voltage - Hu, Chen; Chen, Haiyan; Tang, Aihong (Frontiers in Energy Research, 2024)
The random fluctuation of renewable power generation output makes the frequency and voltage of distribution network fluctuate frequently. And the stable operation performance of the system is decreased. Therefore, the sliding mode control (SMC) strategy of grid-forming (GFM) energy storage converter with fast active support of frequency and voltage is proposed in this paper. Firstly, the virtual synchronous generator (VSG) control possessing the superior GFM performance is applied to singlestage neutral point clamped (NPC) converter of energy storage system. Meantime, the improved comprehensive equivalent circuit model of lithium iron phosphate battery and equivalent model of converter are constructed by means of ampere-hour method and Kirchhoff's law. Then, the SMC with fast response and strong robustness is utilized into the current inner-loop controller. Combined with VSG control, the SMC strategy of GFM energy storage converter is proposed, so that the converter could play an active supporting role by quickly adjusting the output power while the frequency and voltage are reduced. Finally, the simulation model of GFM energy storage converter SMC system is established. Through the simulation analyses, it can be seen that the response time of the proposed strategy to complete the active support is about 0.65s.